Prediksi Kebangkrutan Dengan Altman Z-Score dan Harga Saham pada Perusahaan Manufaktur - Hikmah Hikmah (Universitas Muhammadiyah Sidoarjo, 2018)
Bankruptcy Prediction With the Altman Z-Score Method and the stock price on Manufacturing Company. This research aims to analyze the bankruptcy prediction on stock prices in manufacturing company of basic industry sector and chemical sub-sector of metals that listed in Indonesia Stock Exchange for the period of 2015-2017. The sampling method was done with purposive sampling which then determined 15 companies as sample. Sources of data used are secondary data in the form of financial report published in BEI. Data analysis used data panel regression using eviews version 8. These result shows that Altman Z-Score variable: 1) Working capital to total assets, 2) Retained earning to total assets, 3) Earning before interest and taxes to total assets, 4) Market value of equity to book value of total debts, and 5) Sales to total assets significantly influence stock prices in the metal subsector on the Indonesia Stock Exchange, the average company is in the gray area